Does the Provision of Assistive Technology Increase Disability Employment? - Rahmatika, Rizka Astari; Pratiwi, Chairani Putri; Basuki, Carola (Indonesian Journal of Disability Studies, 2022)
This paper examines various literature regarding the relationship between the provision of assistive technology (AT) and workplace integration for people with disabilities (PwD). A systematic review was conducted to map existing literature using the PRISMA framework in the last ten years. This study reveals that AT has an enormous significance in the employment of PwD. However, the provision of AT as workplace accommodations is not always uncomplicated as three aspects mainly impact it: employers’ perspective, accessibility of AT, and the availability of support from vocational and rehabilitation services. It is suggested that the provision of AT as workplace accommodations to increase disability employment should be supported collectively by society, with employers and the government as critical players. This study contributes to the perspectives of managers and the government by highlighting the roles they could carry out to create a more accessible provision of AT and an inclusive work environment.